Financial literacy and financial behavior with the mediating effect of family financial socialization in the financial institutions of Lahore, Pakistan - Sumaira Khawar; Aamir Sarwar (Future Business Journal, 2021)
Purpose: The main purpose of this study was to find out the relationship between financial literacy and financial behavior and to discover the mediating influence of family financial socialization on this relationship. The study also particularizes that how personal knowledge of finance of an employee and whatever they have learned through family socialization will help them to make sound decisions having a financial impact on them and their family. Design/methodology/approach: Employees of financial institutions employed and residing in Lahore, Pakistan, were the target population of this report. It was a cross-sectional quantitative research study. By using a detailed questionnaire, primary data were obtained. The sample size was 330; through convenience sampling, employees employed in banks were chosen. Descriptive analysis, parametric test, reliability test, and correlational examination with the aid of SPSS 23 and the use of SmartPLS 3.0. are knowledge investigation techniques used in this examination study to infer outcomes. Results/findings: The outcomes which are created from this exploration include: (1) there was no distinction in the financial conduct of representatives from various socioeconomics gatherings. Financial education has a critical positive relationship with financial behavior. (2) Family financial socialization additionally shows a huge positive relationship with financial education and financial behavior. (3) Financial education demonstrated a remarkable abnormal impact on financial behavior through family financial socialization. (4) Family financial socialization shows partial mediation between financial literacy and financial behavior. We can accomplish that formal, as well as informal, training of finance decides the financial behavior of people. Originality/value: This study is the first of this kind to examine the association between financial literacy, and financial behavior using family financial socialization as a mediator and employees of financial institutions as the target population.
Keywords: 650; Family financial socialization; Financial behavior; Financial institutions; Financial literacy